Electrochemical Quantification of Neurotransmitters in Single Live Cell Vesicles Shows Exocytosis is Predominantly Partial. (11th November 2020) - Wang, Ying; Ewing, Andrew
Abstract: Exocytosis plays an essential role in the communication between cells in the nervous system. Understanding the regulation of neurotransmitter release during exocytosis and the amount of neurotransmitter content that is stored in vesicles is of importance, as it provides fundamental insights to understand how the brain works and how neurons elicit a certain behavior. In this minireview, we summarize recent progress in amperometric measurements for monitoring exocytosis in single cells and electrochemical cytometry measurements of vesicular neurotransmitter content in individual vesicles. Important steps have increased our understanding of the different mechanisms of exocytosis. Increasing evidence is firmly establishing that partial release is the primary mechanism of release in multiple cell types. Abstract : Partial release mechanism of exocytosis : This minireview highlights the recent progress in amperometric measurement for monitoring exocytosis from single cells, and electrochemical cytometry measurement of vesicular neurotransmitter content in individual vesicles. Evidence from several studies supports the hypothesis that partial release is the primary mechanism during regular exocytosis.